A comprehensive pan-cancer analysis of the expression characteristics, prognostic value, and immune characteristics of TOP1MT - Fei, Lihong; Lu, Zhimin; Xu, Yufen; Hou, Guoxin (Frontiers in Genetics, 2022)
Background: Mitochondria are at the heart of a number of metabolic pathways providing enormous energy for normal cell growth and regulating tumor cell growth as well as survival. Mitochondrial topoisomerase I (TOP1MT) is a type IB topoisomerase found in the mitochondria of vertebrates. However, no pan-cancer analysis of TOP1MT has been reported. This study aims to explore TOP1MT expression in pan-cancer tissues and identify whether it can be a target for mitochondrial anticancer therapy. Methods and results: The original TOP1MT expression data in 33 different types of cancer patients were downloaded from the TCGA and GTEx databases. TOP1MT was highly expressed in cancer tissues, including BLCA, BRCA, CHOL, COAD, DLBC, ESCA, GBM, HNSC, KIRC, KIRP, LGG, LIHC, LUAD, LUSC, PAAD, PCPG, PRAD, READ, SKCM, STAD, THYM, UCEC, and UCS. According to Kaplan-Meier survival curve analysis, high TOP1MT expression in BLCA, HNSC, KIRP, PAAD, UCEC, and LIHC cancer tissues was linked to poor prognosis of cancer patients, i.e., poor OS, disease-specific survival, and PFI. Linkedomics analysis identified a positive correlation of TOP1MT expression with CNA, but a negative correlation with methylation. TOP1MT expression significantly correlated with immune cells and immune checkpoints in the TIMER database. Functional analysis showed a close relationship between TOP1MT expression and ribosomes. Conclusion: In summary, TOP1MT is a potential biomarker for mitochondrial anticancer therapy and cancer immunotherapy.